1993
DOI: 10.1128/aem.59.4.1162-1167.1993
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alternative electron acceptors on the anaerobic biodegradability of chlorinated phenols and benzoic acids

Abstract: Nitrate, sulfate, and carbonate were used as electron acceptors to examine the anaerobic biodegradability of chlorinated aromatic compounds in estuarine and freshwater sediments. The respective denitrifying, sulfidogenic, and methanogenic enrichment cultures were established on each of the monochlorinated phenol and monochlorinated benzoic acid isomers, using sediment from the upper (freshwater) and lower (estuarine) Hudson River and the East River (estuarine) as source materials. Utilization of each chlorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 39 publications
(36 reference statements)
2
42
2
1
Order By: Relevance
“…In contrast, 3,5-dibromo-4-hydroxybenzoate, the aerobic metabolite of bromoxynil, was degraded under all four anaerobic conditions tested. This is consistent with previous studies with halogenated benzoic acids, specifically their utilization under denitrifying conditions [15,[27][28][29]. No intermediates were detected, and thus the biotransformation pathway of 3,5-dibromo-4-hydroxybenzoate was not elucidated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, 3,5-dibromo-4-hydroxybenzoate, the aerobic metabolite of bromoxynil, was degraded under all four anaerobic conditions tested. This is consistent with previous studies with halogenated benzoic acids, specifically their utilization under denitrifying conditions [15,[27][28][29]. No intermediates were detected, and thus the biotransformation pathway of 3,5-dibromo-4-hydroxybenzoate was not elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Very little is known about transformation of bromoxynil under anaerobic conditions and how biodegradability is affected by different redox conditions. Previous studies have shown that many halogenated aromatic compounds can be degraded under nitrate-reducing, Fe(III)-reducing, sulfidogenic, selenate-reducing, and methanogenic conditions [13][14][15][16][17]. For example, transformation of the herbicide 2,4-dichlorophenoxyacetic acid has been demonstrated under anaerobic conditions both in the presence and absence of sulfate [13].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is desirable to completely mineralize PCP and chlorophenols under anaerobic conditions. In the past two decades, the anaerobic oxidation of phenol and monochlorinated phenols (possible PCP anaerobic reductive dechlorination products) has been described under denitrifying, sulfate-reducing, iron-reducing, or methanogenic conditions (Bae et al, 2002;Evans and Fuchs, 1988;Häggblom and Young, 1993;Kazumi et al, 1995). A number of pure phenol-degrading cultures that use nitrate or sulfate as electron acceptors have been isolated (Bak and Widdel, 1986;Boopathy, 1995;Tschech and Fuchs, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Denitrifying enrichment cultures were established under strictly anaerobic conditions according to the method of Häggblom et al [15] using an inoculum from the Arthur Kill tidal strait in New Jersey, USA. This site is heavily impacted by petroleum hydrocarbons and other anthropogenic contaminants.…”
Section: Enrichmentsmentioning
confidence: 99%